Health care waste management among health workers and associated factors in primary health care facilities in Kampala City, Uganda: a cross-sectional study - Solomon Tsebeni Wafula; Julian Musiime; Frederick Oporia (BMC, 2019)
Abstract Background Healthcare wastes (HCWs) are one of the most hazardous wastes globally; second to only radiation waste. HCW management needs to be prioritized because of the devastating effects on human health and environment if not well managed. Health workers play a crucial role in management of HCWs. This study investigated the management of HCWs among health workers and associated factors in primary health care facilities in Kampala City, Uganda. Methods We conducted a cross-sectional health facility survey in 8 primary health care facilities in Kampala City from March to April 2017. We interviewed health workers who provided data on socio-demographic characteristics, knowledge, attitudes and practices on HCW management. Prevalence ratios (PRs) and their corresponding 95% confidence intervals were used as a measure of association between HCW management and associated factors. The PRs were obtained using a multivariable modified Poisson regression using a generalized linear model of Poisson family with a logarithm as the canonical link function, with robust standard errors while applying a forward elimination method. Results A total of 200 health workers responded to the survey; Knowledge of HCW management  was high 143 (71.5%, 95% CI (65.2-77.8)). About 160 (80.0%) wore appropriate personal protective wear when handling HCWs. Overall, 148 (74.0%, 95% CI (67.8-80.1) had satisfactory HCW management practices. Health workers with diploma education (Adjusted PR = 1.49, 95% CI (1.13-1.96), working in the teenage corner (Adjusted PR = 1.10, 95% CI (1.01-1.29), previous training on HCW management (Adjusted PR = 1.19, 95% CI (1.01-1.42) and those who thought HCW management was important (Adjusted PR = 2.81, 95% CI (1.22-6.47) were more likely to have satisfactory HCW management practices. Conclusion The practices of health workers on HCW management were largely satisfactory. Higher odds of HCW management were determined among health workers with diploma education, previous HCW management trainings and among those who perceived HCW management as important. There is need to organize HCW management trainings in order to improve their HCW management practices among health workers.